UNIT 21.30 BioTAP‐XL: Cross‐linking/Tandem Affinity Purification to Study DNA Targets, RNA, and Protein Components of Chromatin‐Associated Complexes. Issue 1 (5th January 2015) - Alekseyenko, Artyom A.; McElroy, Kyle A.; Kang, Hyuckjoon; Zee, Barry M.; Kharchenko, Peter V.; Kuroda, Mitzi I.
Abstract : In order to understand how chromatin complexes function in the nucleus, it is important to obtain a comprehensive picture of their protein, DNA, and RNA components, as well as their mutual interactions. This unit presents a chromatin cross‐linking approach (BioTAP‐XL) that utilizes a special BioTAP‐tagged transgenic protein bait along with mass spectrometry to identify protein complex components, and high‐throughput sequencing to identify RNA components and DNA binding sites. Full protocols are provided for Drosophila cells and for human cells in culture, along with an additional protocol for Drosophila embryos as the source material. A key element of the approach in all cases is the generation of control data from input chromatin samples. © 2015 by John Wiley & Sons, Inc.